Evolution of Flight Muscle Contractility and Energetic Efficiency - Cao, Tianxin; Jin, J.-P. (Frontiers in Physiology, 2020)
The powered flight of animals requires efficient and sustainable contractions of the wing muscles of various flying species. Despite their high degree of phylogenetic divergence, flight muscles in insects and vertebrates are striated muscles with similarly specialized sarcomeric structure and basic mechanism of contraction and relaxation. Comparative studies on the similarities as well as unique features of different flight muscles together with other striated muscles can provide valuable insights into the fundamental mechanisms of muscle contraction and energetic efficiency. Here we conducted a literature review and data mining to investigate the independent emergence and evolution of flight muscles in insects, birds, and bats, and the likely molecular basis of their contractile features and energetic efficiency. One focus was to assess how and why bird and bat flight muscles are very different in metabolic rates reflecting their different energetic efficiencies while they have evolved based on similar contractile machinery and under the selection of similar natural environments. The significantly lower efficiency of insect flight muscles along with minimized energy expenditure in Ca2+ handling is discussed as a potential mechanism to increase the efficiency of mammalian striated muscles. A better understanding of the molecular evolution of myofilament proteins in the context of physiological functions of invertebrate and vertebrate flight muscles can help explore novel approaches to enhance the performance and efficiency of muscle and heart for the improvement of human health.